Strategi Pengembangan Bisnis Pupuk Organik Padat di Technopark Kebun Raya Massenrempulu Enrekang - Kamba, Ilham; Azis Ambar, Abdul; Nurhapsa, Nurhapsa (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2022)
The fertilizer industry is one of the most promising in agriculture. The rising demand for organic fertilizers shows this industry. The Enrekang Massenrempulu Botanical Garden offers significant organic fertilizer commercial potential. Botanical garden managers must establish an organic fertilizer business plan to preserve their current company. It will also provide alternative strategies and strategic goals for growth in organic fertilizer. This study involves academics, bureaucrats, business players, and consumers. Interviews, field observations, questionnaires, FGDs, and literature research were utilized to gather data. The data analysis methods employed include SWOT and QSPM. With a score of 0.392, Technopark Botanical Gardens Massenrempulu Enrekang's key strength is high product quality. The critical internal strategic aspect is bookkeeping, which has a weighted score of 0.218. Identifying external strategic elements at Technopark Botanical Gardens, Massenrempulu Enrekang enhanced customer purchasing by 0.425. The emergence of a new competitor with a weighted score of 0.172 presents a challenge to Technopark Botanical Gardens Massenrempulu Enrekang. The findings ranked four potential techniques, namely (1). Maintain and increase organic fertilizer quality (2). Using modern information technologies to improve promotion methods (3). Expanding manufacturing capacity and market share.